XIMIYANÍ ÚYRENIWDE LABORATORIYA USÍLLARÍNAN PAYDALANÍW ZÁRÚRLIGI - Kabulova, L.B.; Jumambetova, N.A. (SCIENCE and SOCIETY, 2025)
The article discusses the need to use laboratory methods in the study of chemistry and reveals the special contribution and importance of laboratory work in the scientific study of nature.